2013
DOI: 10.2298/bah1301001p
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Serbian livestock production: Outlook and future

Abstract: The paper describes the state of the livestock production in the Republic of Serbia including preliminary results from the 2012 census: according to preliminary data, 908.990 heads of cattle, 3.403.288 pigs, 1.729.278 sheep and 235.576 goats are reared in Serbia. Structural and institutional measures, and measures of credit support should be the main instruments for achieving the goals of progress in animal husbandry. Activities in the breeding-selection work should be carried out in accordance with the recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Conversely, reports of Cinkulov and coworkers (2008) on genetic diversity and differentiation between two Serbian Tsigai strains revealed substantial differentiation between the two populations, up to the point that authors suggested the two populations to be considered as distinct breeds. Authors' results are contradictory to other reports and to current findings, considering that the Tsigai represents a minority breed in Serbia, with an estimated census of 86 000 breeding animals (Petrovic et al, 2013). Furthermore, results of Cinkulov and coworkers (2008) on the population structure of the Pramenka strains (Svrljig, Dubska and Recka) showed elevated within-population diversity and lack of signatures of admixture between the three strains.…”
Section: Gyimesi Racka and Turcana Considered As One Breedcontrasting
confidence: 89%
“…Conversely, reports of Cinkulov and coworkers (2008) on genetic diversity and differentiation between two Serbian Tsigai strains revealed substantial differentiation between the two populations, up to the point that authors suggested the two populations to be considered as distinct breeds. Authors' results are contradictory to other reports and to current findings, considering that the Tsigai represents a minority breed in Serbia, with an estimated census of 86 000 breeding animals (Petrovic et al, 2013). Furthermore, results of Cinkulov and coworkers (2008) on the population structure of the Pramenka strains (Svrljig, Dubska and Recka) showed elevated within-population diversity and lack of signatures of admixture between the three strains.…”
Section: Gyimesi Racka and Turcana Considered As One Breedcontrasting
confidence: 89%
“…In the period from 2004 to 2015, average production of pork meat was 261 thousand tons, followed by beef, poultry and sheep meat with average production of 87, 82 and 24 thousand tons, receptively. According to Petrović et al (2013) besides a number of important characteristics of pigs, one of them, which is different from other domestic animals is a considerable amount of meat that can be produced per sow per year (more than 2,000 kg of live weight of fatteners or over 1,600 kg of carcass sides or more than 800 kg of meat).…”
Section: Production and Trade Performances Of Pork Meat In Serbiamentioning
confidence: 99%
“…Additionally, increasing the competitiveness of Serbian livestock production can be achieved by creating the conditions for the market environment through investment, both in knowledge and in equipment. Therefore, structural and institutional measures, and measures of credit support should be the main instruments for achieving this goal (Petrović et al, 2013).…”
Section: Production and Trade Performances Of Pork Meat In Serbiamentioning
confidence: 99%
“…Serbia has the possibility of exporting beef meat (baby beef) under preferential conditions in the European Union, but its realization is seriously endangered due to the long-term reduction of cattle production. The total average annual production of beef for the past twenty years in Serbia was about 110,000 tons, with a tendency of decline, especially in recent years, and the latest data show that it is about 80,000 tons (Petrović et al, 2013). Bearing this in mind, further improvement of the structure of Serbian exports of agro-food products from Serbia should be based on greater participation of livestock products, as well as other agro-food products with a higher degree of processing.…”
Section: Main Characteristics Of Agro-food Sector -Observations For Smentioning
confidence: 99%